2008
DOI: 10.1029/2007jb005458
|View full text |Cite
|
Sign up to set email alerts
|

On the rise of turbulent plumes: Quantitative effects of variable entrainment for submarine hydrothermal vents, terrestrial and extra terrestrial explosive volcanism

Abstract: [1] The maximum height reached by a turbulent plume rising in a stratified environment is a key tool to estimate the flux released at its source, particularly for large-scale flows because flux can often be very hard to measure directly. This height is known to be mainly controlled by the stratification of the ambient fluid, source buoyancy flux, and the efficiency of turbulent mixing between the plume and the external fluid. The latter effect has been only superficially explored in spite of its fundamental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 90 publications
(198 reference statements)
0
104
0
Order By: Relevance
“…This implies that the rise height seems to be a function of heat flux only, when heat is fully conserved as in our model. The error in maximum rise height for the scaling expression is about 50% according to Carazzo et al [2008] and we suggest that the lack of heat conservation might explain part of the error, although further studies are required in order to draw definite conclusions.…”
Section: Appendix A: Model Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the rise height seems to be a function of heat flux only, when heat is fully conserved as in our model. The error in maximum rise height for the scaling expression is about 50% according to Carazzo et al [2008] and we suggest that the lack of heat conservation might explain part of the error, although further studies are required in order to draw definite conclusions.…”
Section: Appendix A: Model Comparisonmentioning
confidence: 99%
“…A constant entrainment coefficient has been employed in many other studies [e.g., McDougall, 1990;Rudnicki and Elderfield, 1992;Speer and Rona, 1989]. Carazzo et al [2008], however, showed that a more sophisticated buoyancy dependent entrainment parameterization yields more accurate model results. Unfortunately, the implementation of a variable entrainment reduced our model run speed to such an extent that the large number of model runs carried out here would have been impractical.…”
Section: Appendix A: Model Comparisonmentioning
confidence: 99%
“…where C 1 , C 2 and C 3 are the proportionality constants [e.g., Morton et al, 1956;Sparks, 1986;Carazzo et al, 2008].…”
Section: The 1-d Plume Model Of Eruption Columnmentioning
confidence: 99%
“…Where Ri is the Richardson number and C = shear stress, parameters A and B depend on flow properties, and specifically describe the shapes of velocity, buoyancy, and turbulent shear stress profiles while in the upper plume R = radius and U = velocity (Carazzo et al, 2008).…”
Section: Drag Zone Between Vortex and Seawatermentioning
confidence: 99%
“…Drag at the edge of the plume is responsible for mixing inward from the margin of the plume via the entrainment coefficient α e , a constant proportional to the velocity at a particular elevation (Carazzo et al, 2008):…”
Section: Drag Zone Between Vortex and Seawatermentioning
confidence: 99%